2011
DOI: 10.1371/journal.pone.0019428
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Mapping of DNA Methylation in Chicken

Abstract: Cytosine DNA methylation is an important epigenetic modification termed as the fifth base that functions in diverse processes. Till now, the genome-wide DNA methylation maps of many organisms has been reported, such as human, Arabidopsis, rice and silkworm, but the methylation pattern of bird remains rarely studied. Here we show the genome-wide DNA methylation map of bird, using the chicken as a model organism and an immunocapturing approach followed by high-throughput sequencing. In both of the red jungle fow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
121
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(155 citation statements)
references
References 30 publications
(48 reference statements)
30
121
0
4
Order By: Relevance
“…This is consistent with the observation that average methylation patterns were the lowest in CpG islands that are localized in the promoters [75]. Slight methylation variations were observed along the gene body [74]. It was found that the methylation density in introns was higher than in untranslated transcribed regions (UTRs) and exons within the gene body [75].…”
Section: The Chicken Dna Methylation Landscapesupporting
confidence: 89%
See 2 more Smart Citations
“…This is consistent with the observation that average methylation patterns were the lowest in CpG islands that are localized in the promoters [75]. Slight methylation variations were observed along the gene body [74]. It was found that the methylation density in introns was higher than in untranslated transcribed regions (UTRs) and exons within the gene body [75].…”
Section: The Chicken Dna Methylation Landscapesupporting
confidence: 89%
“…These results followed the same trend as DNA methylation profile in human (for a review see [76]). Methylation level was shown to vary among tissues, the hepatic DNA of red jungle fowl being found to be less methylated than the one of the muscle [74]. This methylation variation between tissues could play a role in the regulation of gene expression during tissue differentiation [77].…”
Section: The Chicken Dna Methylation Landscapementioning
confidence: 93%
See 1 more Smart Citation
“…This CGI contained a CG percentage of 73.5% and an observed to expected CpG ratio of 0.895. In mammals and chicken, approximately 50-65% of transcription starts sites (TSS) overlap with CGI predictions (Li et al 2011;Hu et al 2013;Long et al 2013), which is seen here for DRD4 too. However, the CGI in the great tit DRD4 shows features of both a TSS CGI but also gene body CGI as it overlaps TSS, exon 1 and part of intron 1.…”
Section: Drd4 Methylation Patternsupporting
confidence: 51%
“…The fact that WL but not RJF had a significant overlap between parental and offspring methylation patterns could also be an effect of the domestication process and importance of DNA methylation regulation on expression. The missing association between hypermethylation and downregulation of gene expression is puzzling, as previous studies have reported such correlations [157]. This could be explained by variation within promoters affecting interactions with methyl-CpG binding proteins in a complex manner [158].…”
Section: Dna Methylation Differencesmentioning
confidence: 99%